Measurement and analysis of carotid blood flow and ECG in cardiac - Katai, Mizuki; Noor Azmi, Azran Azhim; Kamiya, Tatsuaki; Akutagawa, Masatake; Hirao, Yuji; Yamaguchi, Hisao; Yoshizaki, Kazuo; Nomura, Masaharu; Obara, Shigeru; Tanaka, Hiroyuki; Kinouchi, Yohsuke (Springer Berlin Heidelberg, 2007)
Dynamics of blood flow in vivo vary with cardiovascular disease. To examine dynamics change of blood flow is useful in the prevention of cardiovascular disease. This study is aimed to investigate the common carotid blood velocity (CCBV) in the cardiac patients. It was performed in 14 cardiac patients (mean ± SD age 68.5 ± 8.3) and 8 healthy subjects as control (age 22.8 ± 1.6). The variations of CCBV were measured using a telemetry blood flow velocimeter system in real time display that was completely developed in our laboratory. This measurement system is based on continuous wave (CW) Doppler ultrasound using two transducers which one is for transmitting and the other one is for receiving. In the report, data were measured for 90 seconds at the rest sitting posture with synchronized measurement of electrocardiogram (ECG) signal. Electromechanical delay (Δt) between ECG signal and CCBV were measured from time of R-wave (Tr) to time of the peak systolic blood velocity (T1). The Δt was 0.169 ± 0.008 s in the healthy subjects. While, the Δt was 0.131 ± 0.016 s in the hypertensive. The delay decreased relatively in the hypertensive. It was coincided with decreases of the magnitude of the peak of diastolic velocities. Furthermore, an acceleration index (AI) and a peak systolic velocity (S1) had correlation in the cardiac patient. The value of AI and S1 decreased particularly. The results suggest that the Δt is affected by arterial properties that may be related to arteriosclerosis.